2021
DOI: 10.1073/pnas.2115116118
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-SID: Identifying EZH2 as a druggable target for desmoid tumors via in vivo dependency mapping

Abstract: Cancer precision medicine implies identification of tumor-specific vulnerabilities associated with defined oncogenic pathways. Desmoid tumors are soft-tissue neoplasms strictly driven by Wnt signaling network hyperactivation. Despite this clearly defined genetic etiology and the strict and unique implication of the Wnt/β-catenin pathway, no specific molecular targets for these tumors have been identified. To address this caveat, we developed fast, efficient, and penetrant genetic Xenopus tropicalis desmoid tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…49 In recent years, tazemetostat (EZH2 inhibitor) is found to have therapeutic effects on DTs in animal models, and in vitro experiments reveal that tazemetostat could directly inhibit the transcription of Wnt/β-catenin pathway in human sclerofibrosarcoma cells. 50 It is found that DTs lack relevant immune markers and almost all specimen tumor cells are negative for PD-L1, and PD-1 is only partially expressed in lymphocytes surrounding the tumor. 51 This suggests that immune checkpoint inhibitors may not be indicated for the treatment of DTs.…”
Section: Other Drugsmentioning
confidence: 97%
See 1 more Smart Citation
“…49 In recent years, tazemetostat (EZH2 inhibitor) is found to have therapeutic effects on DTs in animal models, and in vitro experiments reveal that tazemetostat could directly inhibit the transcription of Wnt/β-catenin pathway in human sclerofibrosarcoma cells. 50 It is found that DTs lack relevant immune markers and almost all specimen tumor cells are negative for PD-L1, and PD-1 is only partially expressed in lymphocytes surrounding the tumor. 51 This suggests that immune checkpoint inhibitors may not be indicated for the treatment of DTs.…”
Section: Other Drugsmentioning
confidence: 97%
“…In recent years, tazemetostat (EZH2 inhibitor) is found to have therapeutic effects on DTs in animal models, and in vitro experiments reveal that tazemetostat could directly inhibit the transcription of Wnt/β-catenin pathway in human sclerofibrosarcoma cells. 50…”
Section: Treatmentmentioning
confidence: 99%
“…A substantial contribution to the field of tumorigenesis research was made by Naert et al (2021) , who introduced CRISPR-SID. This approach integrated multiplexed CRISPR-Cas9 genome editing with deep learning, predicting double-strand break repair patterns to identify genes vital for tumorigenesis, suggesting a druggable potential of key genes.…”
Section: Deep Learning For Prediction Of Crispr-cas Editing Outcomesmentioning
confidence: 99%
“…Mimicking missense variants will have a very high impact on the field, since a large proportion of disease variants are missense by nature. Base editing, which changes a single base without cutting the DNA backbone and is, therefore, perfectly suited to missense modelling ( Komor et al, 2016 ), has been shown to work in Xenopus ( Shi et al, 2019 ; Park et al, 2017 ; Naert et al, 2020 and 2021b ). Xenopus are particularly suited for this type of modelling due to the ease of generating many mutant lines.…”
Section: Introductionmentioning
confidence: 99%